2005
DOI: 10.1002/ijc.21427
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Transactivation of the ICAM‐1 gene by CD30 in Hodgkin's lymphoma

Abstract: The ICAM-1/LFA-1 complex mediates cell-cell interaction. ICAM-1 is overexpressed in Hodgkin/Reed-Sternberg (H/RS) cells, and serum levels of its soluble form are higher in Hodgkin's lymphoma (HL) patients than in controls. There are no data, however, regarding the regulation of expression of ICAM-1 in H/RS cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 51 publications
(97 reference statements)
0
6
0
Order By: Relevance
“…Additionally, the expression of MMP9 by human promyelocytic leukemia HL-60 cell line has been associated with intercellular adhesion molecule-1 (ICAM-1) shedding into the cell medium [28], which would suggest another explanation. ICAM-1, which is overexpressed by HRS cells [29], regulates leukocyte homing, activation, and effector functions like T-cell and Natural Killer (NK) cell-mediated cytotoxicity. ICAM-1 shedding by tumor cells into the microenvironment might be associated with T/NK-cell mediated death resistance, since soluble ICAM-1 would act as a decoy ligand, binding surface receptors of NK-cells and preventing them from recognizing molecules displayed on the surface of the tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the expression of MMP9 by human promyelocytic leukemia HL-60 cell line has been associated with intercellular adhesion molecule-1 (ICAM-1) shedding into the cell medium [28], which would suggest another explanation. ICAM-1, which is overexpressed by HRS cells [29], regulates leukocyte homing, activation, and effector functions like T-cell and Natural Killer (NK) cell-mediated cytotoxicity. ICAM-1 shedding by tumor cells into the microenvironment might be associated with T/NK-cell mediated death resistance, since soluble ICAM-1 would act as a decoy ligand, binding surface receptors of NK-cells and preventing them from recognizing molecules displayed on the surface of the tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the remarkable correlation between CD69 and ICAM-1 expression indicates that the latter molecule may be used as a sensitive NK cell activation marker. However, an exception was observed by the TLR2 agonist, Pam 3 CyS, which was able to induce CD69 expression but failed to up-regulate ICAM-1, suggesting an independent mechanism for modulation of these two activation markers [47].…”
Section: Discussionmentioning
confidence: 94%
“…In addition, the remarkable correlation between CD69 and ICAM-1 expression indicates that the latter molecule may be used as a sensitive NK cell activation marker. However, an exception was observed by the TLR2 agonist, Pam 3 CyS, which was able to induce CD69 expression but failed to up-regulate ICAM-1, suggesting an independent mechanism for modulation of these two activation markers [47].Recent studies have demonstrated that human NK cells efficiently enhance CD4 1 as well as CD8 1 T-cell proliferation. This process is dependent on direct contact-mediated interactions between ligands for TCR co-stimulatory receptors expressed on stimulated human NK cells such as CD80, CD86, CD70, OX40L and 2B4 receptors [16,17,48].…”
mentioning
confidence: 99%
“…Despite the presence of overlapping bands, probably due to heterogeneity of glycans present on individual glycoproteins, multiple glycoproteins were identified, including the dendritic and epithelial cell receptor DEC-205 (CD205) and intercellular adhesion molecule 1 (ICAM-1) (Figure 3 and Additional file 1). DEC-205 and ICAM-1 are both heavily glycosylated proteins known to be expressed in HRS cells [13,14]. The heavy chain of the cell surface molecule CD98 (CD98hc) was identified across a region of the gel between approximately 75 and 100 kDa and the accompanying small chain LAT1 was also detected, but below confidence levels for the analysis (Additional file 1).…”
Section: Resultsmentioning
confidence: 99%